Impact of changes in circulation and melting from the Patagonian ice caps on the regulation of atmospheric CO2 by the Southern Ocean - (:unkn) unknown (My University, 2025)
Proyectos de Intercambio Programa de Cooperación Cientifica ECOS, CONICYT, Programa de Cooperación Internacional, Convocatoria 2015. Proyecto código: C15U04